Pengembangan Media Pembelajaran Bangun Ruang Berbasis Adobe Flash Pada Siswa Sekolah Dasar Pulubala - Abubakar, Nurfadila; Pulukadang, Wiwy Triyanty; Marshanawiah, Andi (Jurnal Studi Guru dan Pembelajaran, 2024)
The problem identified at SDN 16 Pulubala is the lack of teacher creativity inutilizing spatial geometry learning media, which leads to a lack of interest and motivation among students in learning mathematics. Therefore, the development of spatial geometry learning media is expected to help students comprehending the material on the spatial geometry. This research is a Research and Development (R&D). The objectives of this research and development are to develop adobe flash-based spatial geometry learning media and to assess its feasibility based on expert evaluations of content, media, and feedback from teachers and students. The research method used is the Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data analysis techniques employed in this research are descriptive and qualitative. The results of the development of Adobe Flash-based spatial geometry learning media indicate that the feasibility aspects have achieved a very feasible category, with an average rating of 87,5% from content experts and 95%from media experts, making it suitable for trial. Furthermore, based on teacher feedback, the Adobe Flash-based spatial geometry learning media received 92,85% in the very feasible category, while student responses averaged 92,60%, also in the very high category. The media evaluation achieved an 87,42% score in the very high category. Thus, the overall score recapitulation is 91,074%. Therefore, the developed Adobe Flash-based spatial geometry learning media is highly suitable for use in teaching and learning activities.